2015
DOI: 10.1371/journal.pone.0145161
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Cognitive-Motor Step Training Improves Cognitive Risk Factors of Falling in Older Adults – A Randomized Controlled Trial

Abstract: PurposeInteractive cognitive-motor training (ICMT) requires individuals to perform both gross motor movements and complex information processing. This study investigated the effectiveness of ICMT on cognitive functions associated with falls in older adults.MethodsA single-blinded randomized controlled trial was conducted in community-dwelling older adults (N = 90, mean age 81.5±7) without major cognitive impairment. Participants in the intervention group (IG) played four stepping games that required them to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
158
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(179 citation statements)
references
References 55 publications
2
158
1
4
Order By: Relevance
“…For example, dancing has been shown to positively influence coordinative skills and balance, whereas strength training with exercises similar to the ones incorporated in our intervention has been demonstrated to be effective in older adults (119)(120)(121)(122). Also after step-based games, requiring the execution of rapid and welldirected steps, improvements in balance have been reported (123,124). Moreover, in a previous pilot study of the Active@Home exergame (59), heart rate measures during training showed moderate physical intensity (an average heart rate of about 60% of the estimated maximal heart rate of the elderly participants), which is recommended to improve cardiovascular fitness (68).…”
Section: Training Effects On Physical Functionsmentioning
confidence: 81%
“…For example, dancing has been shown to positively influence coordinative skills and balance, whereas strength training with exercises similar to the ones incorporated in our intervention has been demonstrated to be effective in older adults (119)(120)(121)(122). Also after step-based games, requiring the execution of rapid and welldirected steps, improvements in balance have been reported (123,124). Moreover, in a previous pilot study of the Active@Home exergame (59), heart rate measures during training showed moderate physical intensity (an average heart rate of about 60% of the estimated maximal heart rate of the elderly participants), which is recommended to improve cardiovascular fitness (68).…”
Section: Training Effects On Physical Functionsmentioning
confidence: 81%
“…Dancing exercises were based on common dances as Bachata, Disco Fox, Salsa, Waltz, Cha-Cha-Cha, and Jive and, in general, require motor components of balance, coordination, and agility, but also cognitive resources [45][46][47]. Dancing and the execution of rapid and welldirected steps has been shown to improve balance, coordinative skills, endurance and cognitive functions [48][49][50][51][52][53]. Both, Tai Chi and dancing are "holistic" and taskoriented physical activities [54,55].…”
Section: Exergame Interventionmentioning
confidence: 99%
“…In addition to this, it has been shown that exergames including cognitive and motor training, induce comparable improvements in physical function to more traditional forms of exercise delivery [8,10]. More importantly, studies using stepping exergames have improved both physical and cognitive fall risk factors in older people [7,11,12].…”
Section: Introductionmentioning
confidence: 98%